Safety and efficacy analysis of microwave ablation in small hepatocellular carcinomas sized below 3 cm - Piskin, Ferhat C. (Pol J Radiol, 2020)
PURPOSE: The aim of this study was to investigate the efficacy and safety of microwave ablation (MWA) in small hepatocellular carcinomas sized ≤ 3 cm, determine long-term survival, and identify prognostic factors for survival rates. MATERIAL AND METHODS: In this study, the radiological and laboratory findings obtained from 31 consecutive patients who underwent MWA were retrospectively evaluated. The survival periods and complication rates were analysed. RESULTS: Microwave ablation was applied to 42 hepatocellular carcinoma nodules in 31 patients. The mean age of the patients was 61 ± 7.3 (median 62, range 46-78) years. The mean overall survival (OS) was 47.4 ± 3.3 months. The rates of cumulative OS in the first, second, and third years were 95.2%, 91.8%, and 79.2%, respectively. The mean disease-free survival (DFS) rate was 24.1 ± 2.5 months. The cumulative DFS rates in the first, second, and third years were 75.6%, 52.5%, and 28.2%, respectively. The number of tumours and tumour distribution were determined as prognostic factors. No major complication was detected, but six patients (13.9%) developed minor complications after MWA. CONCLUSIONS: Microwave ablation in patients with hepatocellular carcinoma is a safety treatment modality with very low rates of complications. It offers an effective treatment with a high rate of complete response and local disease control according to the short-term results. In the long term, it prolongs the survival time of the treated patients. The number of tumours and tumour distribution were determined as prognostic factors affecting survival rates.